The future of translational research on alcohol use disorder. (14th April 2020) - Ray, Lara A.; Grodin, Erica N.; Leggio, Lorenzo; Bechtholt, Anita J.; Becker, Howard; Feldstein Ewing, Sarah W.; Jentsch, James David; King, Andrea C.; Mason, Barbara J.; O'Malley, Stephanie; MacKillop, James; Heilig, Markus; et al.
Abstract: In March 2019, a scientific meeting was held at the University of California, Los Angeles (UCLA) Luskin Center to discuss approaches to expedite the translation of neurobiological insights to advances in the treatment of alcohol use disorder (AUD). A guiding theme that emerged was that while translational research in AUD is clearly a challenge, it is also a field ripe with opportunities. Herein, we seek to summarize and disseminate the recommendations for the future of translational AUD research using four sections. First, we briefly review the current landscape of AUD treatment including the available evidence‐based treatments and their uptake in clinical settings. Second, we discuss AUD treatment development efforts from a translational science viewpoint. We review current hurdles to treatment development as well as opportunities for mechanism‐informed treatment. Third, we consider models of translational science and public health impact. Together, these critical insights serve as the bases for a series of recommendations and future directions. Towards the goal of improving clinical care and population health for AUD, scientists are tasked with bolstering the clinical applicability of their research findings so as to expedite the translation of knowledge into patient care. Abstract : This manuscript summarizes and disseminates recommendations for the future of translational research in alcohol use disorder. It reviews the landscape of alcohol use disorder treatment and discusses treatment development opportunities. It also considers various models of translational science and provides a series of recommendations for research in the field.